Risk Factors of Neonatal Sepsis in DHQ Hospital Skardu - Muhammad Bashir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Sepsis is a substantial cause of newborn illness and death. Few aspects of sepsis' clinical impact and risk factors are thoroughly recognized. Late-onset sepsis is linked to healthcare-associated infections and affects newborns older than seven days. Aim: To evaluate the clinical outcome and risk variables related to newborn sepsis at the DHQ hospital Skardu in Pakistan. Methods: A quantitative retrospective institution-based chart review was carried out at DHQ Hospital Skardu with a sample size n=225. Results: 164(72.9%l) of the 225 evaluated newborn charts were for newborns less than 7 days old, and 144(64%) were for males. Meconium aspiration syndrome involved forty newborns, or 17.8%, while abnormal respiratory symptoms affected twenty-nine infants or 12.9%. Among newborns diagnosed with neonatal sepsis, therapy resulted in complete recovery for 189(84%) infants, death for 9(4%) infants, and transfer of care to other hospitals for 13(5.7%) infants. Meconium aspiration syndrome and respiratory distress syndrome contributed to the poor prognosis of newborn sepsis (AOR = 0.1989 [0.059-0.664] and AOR = 0.258 [0.072-0.900], respectively). Conclusion: The clinical prognosis for newborn sepsis at DHQ hospital Skardu was worse than desirable. RDS and meconium aspiration syndrome were the most accurate indicators of a poor prognosis in newborn sepsis. It is hypothesized that improved prenatal care, early diagnosis and treatment of neonatal illnesses or abnormalities, and the provision of essential newborn care to all newborns through the end of the neonatal period will all contribute to improved neonatal outcomes. Keywords: Risk factors, treatment, Sepsis, Neonatal, DHQ hospital, Sakrdu, Pakistan